Blended Learning Management: The Efforts to Develop Students’ Soft Skills in the New Normal Era - Diana, Eka; Rahmah, Nafisatur; Rofiki, Moh. (Jurnal Basicedu, 2022)
This study aims to analyze the application of blended learning management in developing students' soft skills in the new normal era. This study uses a qualitative research method with a case study approach. The location of this research is MI Raudlatul Jannah I Maron Probolinggo Data collection is done with primary and secondary data. Preliminary data were obtained through in-depth interviews and observation. At the same time, secondary data is obtained through documents and learning tools. The results showed that the application of blended learning management at MI Raudlatul Jannah I consisted of planning, implementing, and evaluating. The application of blended learning in the new normal era can develop students' soft skills in four aspects, namely discipline, honesty, attitude, and communicativeness.